Legal Analysis Of The Role Of The Police In Murder (A Study At The Medan City Police Office) - Nathanael Marvelino Saragih Sidauruk; Mhd. Azhali Siregar; Aulia Rahman Hakim (JURNAL HUKUM SEHASEN, 2026)
The crime of mugging or theft with violence is a form of street crime that causes unrest in society because it not only causes material losses but also threatens the safety of the victims. In the jurisdiction of the Medan Police, mugging shows an increasing trend and often involves juvenile perpetrators. This condition demands an active role of the police in carrying out comprehensive countermeasures. This study aims to analyze the legal regulations related to the crime of mugging, the role of the police in overcoming the crime of mugging, as well as the obstacles and efforts faced by the Medan Police in handling it. The research method used is empirical juridical legal research with a qualitative descriptive approach. Data were obtained through direct interviews with Medan Police officers and a literature study of relevant laws and legal literature. The results of the study indicate that the crime of mugging is legally regulated in Article 365 of the Criminal Code and Articles 476, 477, and 479 of Law Number 1 of 2023 concerning the Criminal Code. The police's role in combating the crime of mugging is carried out through preventive, repressive, and preemptive efforts, such as patrols in vulnerable areas, law enforcement against perpetrators, and legal counseling to the community. For child perpetrators, the Medan Police apply Law Number 11 of 2012 concerning the Juvenile Criminal Justice System by prioritizing the principle of restorative justice. The main obstacles faced are socioeconomic factors, low public legal awareness, and the less than optimal role of related agencies in prevention efforts. Based on the results of this study, it can be concluded that combating the crime of mugging cannot be solely the responsibility of the police, but requires synergy between law enforcement officers, local governments, and the community to create sustainable security and order.